Analysis Implications of Financial Literacy, Socialization, Experience, Attitude, and Locus of Control on Financial Behavior of University Student - Setiawan, Hendry; Laulita, Nasar Buntu (Universitas Proklamasi 45, 2024)
The economic development of a country must be accompanied by good and responsible public financial behavior, so this research aims to analyze the factors that impact financial behavior. Several factors examined in this research are financial literacy, financial experience, financial attitudes, financial socialization, and locus of control. The samples tested in this study were students studying at Batam International University (UIB), Riau Islands. The research result using a partial test (t-test) indicated that financial literacy, financial experience, financial attitudes, and financial socialization had a significant effect on financial behavior. Meanwhile, locus of control does not affect UIB students' financial behavior.